Trinity of passion : the literary left and the antifascist crusade - Wald, Alan M., 1946- (University of North Carolina Press, 2007)
The second of three volumes that track the political and personal lives of several generations of U.S. left-wing writers, this book carries forward the chronicle launched in 'Exiles from a Future Time: the Forging of the Mid-Twentieth-Century Literary Left'. In this volume, the author delves into literary, emotional, and ideological trajectories of radical cultural workers in the era when the International Brigades fought in the Spanish Civil War (1936-39) and the United States battled in World War II (1941-45).